Communication System in the Organization of the Hajj Worship in North Sumatra, Indonesia - Ahmad Tamrin Sikumbang; Syukur Kholil; Rubino Rubino; Farhan Indra (Khazanah Sosial, 2022)
This article discusses the role of communication in attracting Hajj pilgrims to North Sumatra. This article examines the steps taken by the North Sumatra Province Ministry of Religion to implement a communication system in terms of services and pilgrim protection guarantees. This article's research employs a descriptive method with a qualitative approach. Interviews were conducted with several informants who were considered qualified to answer this topic within the Ministry of Religion of North Sumatra, including the Jemaah Haji from North Sumatra. Literature studies and documentation are two other methods for gathering data. Data processing and analysis techniques were applied in three stages: data reduction, data presentation, and conclusion drawing. According to the findings of this study, the Ministry of Religion has ensured a fair, professional, and accountable implementation of the Hajj by prioritizing the interests of the congregation, and general and special services for disabled people. Meanwhile, both domestically and in Saudi Arabia, coaching takes the form of practice. Furthermore, the Ministry of Religion has put legal safeguards in place to ensure the safety of Hajj pilgrims.